PENGARUH MODEL PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Aam Amaliyah (Universitas Muhammadiyah Gresik, 2020)
This research aims to determine whether or not there is a difference of problem solving ability mathematics with realistic mathematic education learning model to problem solving skill in math. The type of this research is experimental research with quasi experimental design and nonequivalent control group design’s type. This research was conducted at SDN Poris Pelawad 3 Cipondoh Kota Tangerang class IV in the even semester of academic year 2018/2019. The sample was 20 students consisting 20 experiment class students and 20 control class students. The results of the research explained that a difference in the ability of a mathematical problem solver between the control class and the experimental class.